The application of infection control in intraoral radiographic examinations in various healthcare facilities: an observational study - Prihandita, Alifia Rizqy Ramadhania; Shantiningsih, Rurie Ratna; Gracea, Rellyca Sola; Mudjosemedi, Munakhir (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: One of the sectors that has been significantly impacted by the COVID-19 pandemic is dentistry. There is a significant chance that an intraoral radiographic examination will facilitate the spread of the COVID-19. One of the radiographers' efforts to prevent the spread of the COVID-19 virus is to carry out infection control. The application of infection control performed by radiographers is influenced by many factors. This study aimed to analyze differences in the application of infection control in intraoral radiographic examinations during the COVID-19 pandemic in various healthcare facilities. Methods: This study conducted was an observational analytic study with a cross-sectional design. The research was conducted using a questionnaire consisting of 13 statement items. Thirty intraoral dental radiographers who were employed in radiology departments at various healthcare facilities participated in the study as respondents. The research data that had been collected was then tested using the One Way Anova test to find out the differences in the application of infection control by radiographers from each healthcare facility. Results: The results of the study indicated that the significance value was 0.314 (p>0.05), which means that there was no significant difference in the score category for each healthcare facility. The lack of complete respondents from all different kinds of existing healthcare facilities was still a weakness of this study. Conclusion: During the COVID-19 pandemic, there was no discernible difference in how each healthcare facility implemented infection control during intraoral radiographic examinations.KeywordCOVID-19, healthcare facilities, infection control, intraoral radiographs, radiographers